Pemetaan Lahan Kritis Untuk Analisis Kesesuaian Pemanfaatan Lahan di Kabupaten Kulon Progo - Wirastuti Widyatmanti; Sigit Heru Murti; Prima Dinta Syam (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
Uncontrolled and unsupported changes in land use by good watershed conservation efforts will lead to degradation of watershed quality, caused by declining land functions as buffer zones, both from production and water availability aspects. Therefore, efforts should be made to improve the function and land use so that the watershed quality is in a balanced and sustainable condition. One way that can be implemented to make land use arrangements is to look at the critical aspect of land in the region. This study aims to map critical lands in Kulon Progo regency using spatial data analysis from remote sensing image interpretation and existing thematic maps; and analyze the linkage between existing land use to existing critical land. Spatial analysis is done by overlaying some spatial data (critical land determinants) to generate a new mapping unit to be used as an analytical unit. The scoring method accommodates different types of parameter data available to determine the degree of criticality of the land. The result of the analysis shows that in Kulon Progo Regency 16.7% or 9541,21 ha from the area of the district is uncritical, while 47.8% or 27,397 ha is potentially critical land, or if not managed properly can become critical land; and 35.5% or 20,329 ha are areas with land critical status from somewhat critical, critical to very critical.